Acoustic streaming on antibody-functionalized screen-printed electrode enhances detection sensitivity and total assay duration for voltammetric immunosensing of newcastle disease virus - Abd Muain, Mohamad Farid; Amir Hamzah, Amir Syahir; Chia, Suet Lin; Yusoff, Khatijah; Lim, Hong Ngee; Ikeno, Shinya; Laurell, Thomas; Ahmad Tajudin, Asilah (Elsevier, 2025)
Conventional diagnostic methods often involve long incubation times due to limited fluid mixing in confined spaces, despite offering high sensitivity. Therefore, acoustic streaming was employed to enhance microscale advection, thereby improving biomolecular interactions and reducing assay duration. The micromixing capability was demonstrated by dispersing methylene blue (MB) in deionized water and glycerol solutions, where homogenization time decreased by approximately 80 % in water and 84–88 % in glycerol under acoustic actuation. Biomolecule adsorption was modeled using MB adsorbed onto cellulose acetate–graphene oxide (CA-GO) beads, showing improved adsorption and a reduced time to saturation from 16 to 8 min. Maximum adsorption occurred at 2 MHz frequency and 20 V amplitude. By using these optimized parameters, voltammetric immunosensing of Newcastle disease virus (NDV) was performed on PEG-alkanethiol-modified screen-printed gold electrodes (SPGE). The system incorporating acoustic streaming was compared against one without it. Results demonstrated a comparable limit of detection (1.46 HA μL−1 at 3σ m−1) achieved at shorter assay duration (8 min). These findings underscore the potential of acoustic streaming in electrochemical immunosensors to accelerate diagnostic assays without compromising sensitivity or specificity, particularly for applications utilizing screen-printed electrodes.